FISHPOND AQUACULTURE INVENTORY IN MAROS REGENCY OF SOUTH SULAWESI PROVINCE - Yennie Marini; - Emiyati; Teguh Prayogo; Rossi Hamzah; Bidawi Hasyim (International Journal of Remote Sensing and Earth Sciences (IJReSES), 2013)
Currently, fishpond aquaculture becomes an interesting business for investors because of its profit,  and  a  source  of  livelihood  for  coastal  communities.  Inventory  and  monitoring  of  fishpond aquaculture provide important baseline data to determine the policy of expansion and revitalization of the fishpond. The aim of this research was to conduct an inventory and monitoring of fishpond area inMaros regency of South Sulawesi province using Satellite Pour l’Observation de la Terre (SPOT -4) and Advanced Land Observing Satellite (ALOS) Phased Array type L-band Synthetic Apeture Radar (PALSAR). SPOT image classification process was performed using maximum likelihood supervised classification  method and  the  density  slice  method  for ALOS  PALSAR.  Fishpond  area  from  SPOT data was  9693.58  hectares  (ha),  this  results  have  been  through  the  process  of  validation  and verification by the ground truth data. The fishponds area from PALSAR was 7080.5 Ha, less than the result  from  SPOT  data.  This  was  due  to  the  classification  result  of  PALSAR  data  showing someobjects around fishponds (dike, mangrove, and scrub) separately and were not combined in fishponds area  calculation.  Meanwhile, the  result  of  SPOT -4  image  classification  combined object  around fishponds area.